Low catestatin as a risk factor for cardiovascular disease – assessment in patients with adrenal incidentalomas - Zalewska, Ewa; Kmieć, Piotr; Sobolewski, Jakub; Koprowski, Andrzej; Sworczak, Krzysztof (Frontiers in Endocrinology, 2023)
Background Catestatin (Cts) is a peptide derived from proteolytic cleavage of chromogranin A, which exhibits cardioprotective and anti-inflammatory properties. Cts has been proposed as a potential biomarker for cardiovascular (CV) disease. Objectives examining Cts in patients with incidentally discovered adrenocortical adenomas (AI), and its associations with CV risk factors and blood pressure (BP). Materials and methods In this cross-sectional study, 64 AI patients without overt CV disease other than primary hypertension were recruited along with 24 age-, sex-, and body-mass-index (BMI)-matched controls with normal adrenal morphology. Laboratory, 24-h ambulatory BP monitoring, echocardiography, and common carotid artery sonography examinations were performed. Results Unadjusted Cts was higher in AI patients (median 6.5, interquartile range: 4.9-37 ng/ml) versus controls (4.5 (3.5 – 28)), p=0.048, however, the difference was insignificant after adjusting for confounding variables. Cts was lower in subjects with metabolic syndrome than in those without it (5.2 (3.9- 6.9) vs. 25.7 (5.8-115) ng/ml, p<0.01), and in men compared to women (4.9 (4-7.4) ng/ml vs. 7 (4.8-100), p=0.015). AI patients in the lower half of Cts levels compared to those in the upper had a higher prevalence of hypertension (OR 0.15, 95% CI: 0.041-0.5, p<0.001) and metabolic syndrome (OR 0.15, 95% CI 0.041-0.5, p<0.001). In AI patients Cts correlated positively with high-density lipoprotein cholesterol (Spearman’s r=0.31), negatively with BMI (r=-0.31), and 10-year atherosclerotic CV disease risk (r=-0.42). Conclusions Our data indicate associations between CV risk factors and Cts. More clinical research is needed to apply serum Cts as a biomarker.